A self-compensation procedure for the IEEE 1588 PTP local clock. (1st January 2014) - Liu, Yingshu; Yang, Cheng; Liu, Shupei
Time synchronisation plays an important role in networked measurement and control systems, where high precision of global time resolution are required for distributed data acquisition and control. The Ethernet/IP-based IEEE 1588 precise time protocol (PTP) provides a perfect solution to this requirement. The work of this paper addresses the modelling and simulation of the IEEE 1588 PTP clock implementation, aiming to provide insight on the process of the PTP clock synchronisation, the factors that affect the synchronisation performance as well as the interactions of these factors. The OMNeT++ is chosen as the simulation platform and the end-to-end (E2E)-based double-node scenario is considered. Simulation results show that, the clock synchronisation procedure with frequency skew correction mechanism has enabled a nanosecond precision to be achieved, regardless of the quality of the local timing components and the asymmetry of the transmission path delay.